2020
DOI: 10.5194/acp-20-3859-2020
|View full text |Cite
|
Sign up to set email alerts
|

Global inorganic nitrate production mechanisms: comparison of a global model with nitrate isotope observations

Abstract: Abstract. The formation of inorganic nitrate is the main sink for nitrogen oxides (NOx = NO + NO2). Due to the importance of NOx for the formation of tropospheric oxidants such as the hydroxyl radical (OH) and ozone, understanding the mechanisms and rates of nitrate formation is paramount for our ability to predict the atmospheric lifetimes of most reduced trace gases in the atmosphere. The oxygen isotopic composition of nitrate (Δ17O(nitrate)) is determined by the relative importance of NOx sinks and thus can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
205
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(218 citation statements)
references
References 124 publications
11
205
2
Order By: Relevance
“…And then we can calculate the source apportionment (Zong et al, 2017 Previous studies suggested that the oxidation pathway of NO 3 + HC/DMS (DMS is a major in coastal environments) to form HNO 3 (3) is also very important (Alexander et al, 2009;He et al, 2018;Walters & Michalski, 2016;Wang et al, 2019). However, few studies have quantitatively calculated its contribution (Alexander et al, 2009(Alexander et al, , 2020Wang et al, 2019). In our second model, we used a δ 15 N and δ 18 O array of NO 3 − in PM 2.5 to determine the contributions of all three major oxidation pathways using the MixSIAR model.…”
Section: 1029/2020jd032604mentioning
confidence: 99%
See 1 more Smart Citation
“…And then we can calculate the source apportionment (Zong et al, 2017 Previous studies suggested that the oxidation pathway of NO 3 + HC/DMS (DMS is a major in coastal environments) to form HNO 3 (3) is also very important (Alexander et al, 2009;He et al, 2018;Walters & Michalski, 2016;Wang et al, 2019). However, few studies have quantitatively calculated its contribution (Alexander et al, 2009(Alexander et al, , 2020Wang et al, 2019). In our second model, we used a δ 15 N and δ 18 O array of NO 3 − in PM 2.5 to determine the contributions of all three major oxidation pathways using the MixSIAR model.…”
Section: 1029/2020jd032604mentioning
confidence: 99%
“…Nitrate (NO 3 − ) is an important component of PM 2.5 (aerodynamic diameters <2.5 μm) in many Chinese urban atmospheres (Guo et al, 2020;Huang et al, 2014;Luo et al, 2019;Wang et al, 2019). As a precursor of NO 3 − , NO x (NO and NO 2 ) is a major component of reactive nitrogen in the atmosphere, mainly derived from anthropogenic activities, such as combustion of fossil fuels (Alexander et al, 2009(Alexander et al, , 2020Galloway et al, 2008;Xiao et al, 2015). Tropospheric ozone (O 3 ), formed in the photochemical cycle of NO x , and its byproduct, the hydroxyl radical (OH), largely determine the oxidizing capacity of the atmosphere and the lifetimes of most reduced trace gases (Thompson, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Low Δ 17 O values in atmospheric nitrate were reported by Brothers et al (2008) in Ecuador (13-22‰) and were also observed in Taiwan (3-31‰) (Guha et al, 2017) and the Central TP (7-24‰) (Xia et al, 2019). The extremely low Δ 17 O values in Taiwan have not yet been simulated by a state-of-the-art global chemical transport model (Goddard Earth Observing System-Chem) (Alexander et al, 2009(Alexander et al, , 2020. Such low nitrate Δ 17 O values were also observed in surface snow samples collected from Greenland (~5‰) (Fibiger et al, 2013) and inland Antarctica (~13‰) (Noro et al, 2018) and in an ice core drilled from the Quelccaya Ice Cap at Peru (~6‰) (Buffen et al, 2014), which were interpreted as preserved atmospheric signals.…”
Section: Potential Factors Leading To Low δ 17 O Valuesmentioning
confidence: 99%
“…2b-c). Nighttime production of nitrate by the heterogeneous uptake of N2O5 and NO2 is a major pathway of nitrate production in northern China (Wang et al, 2018;Alexander et al, 2020). The 2-5 times greater concentrations of simulated nitrate at night suggest overpredicted nighttime production, underestimated boundary-layer dilution, or underestimated removal of nitrate.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Moreover, laboratory and field measurements show that the NO2 uptake coefficient (γNO2) on the aerosol surface ranges from 10 -8 to 10 -4 (Spataro and Ianniello, 2014 and references therein; M. Li et al, 2019 and references therein). The default GEOS-Chem model uses a relatively high γNO2 of 10 -4 , which may cause the underestimated NO2 concentrations as well as the overestimated concentrations of HNO3, HONO, and nitrate and needs further evaluation (Alexander et al, 2020). For NH3, the model underestimates its monthly mean concentrations in Beijing (Fig.…”
Section: Potential Contributors To the Model-observation Discrepanciesmentioning
confidence: 99%